Involvement of memory T-cells in the pathophysiology of chronic lymphocytic leukemia - Correia,Rodolfo Patussi (2014)
The role of T-cells in the pathogenesis of chronic lymphocytic leukemia has recently gained much attention due to the importance of the constant interaction between neoplastic B-cells with microenvironment substratum and T-cells. It is believed that these interactions modulate the clinical course of the disease, mainly through the regulation of the expansion, differentiation, and survival of chronic lymphocytic leukemia B-cells. Importantly, this crosstalk may also change the number, function, and memory phenotype of normal T-cells, thereby altering the amplitude and/or efficiency of adaptive immunity in chronic lymphocytic leukemia patients. The present study presents an overview on important aspects of this immunological crosstalk, particularly on the abnormalities of chronic lymphocytic leukemia B-cells and the alterations in normal T-cells, with focus on the CD4 memory T-cell compartment that could offer survival signals to chronic lymphocytic leukemia B-cell clone(s) and contribute to the establishment and progression of the disease. The authors believe that understanding the biological consequences of the interaction between normal T- and neoplastic B-cells in chronic lymphocytic leukemia may allow for improvements in the prognostic information and therapeutic approaches for this disease.